Keefektifan Model Pembelajaran Role Playing dengan Media Video Animasi Terhadap Kemampuan Pemecahan Masalah Matematika - Baeti, Nuari Nur; Prasetiyawati, Dwi; Priyanto, Wawan (UNIB Press, 2020)
The use of role playing learning model can help understanding the concept of students against, math because it involves students in the process learning so that students are not monotonous. In addition, the researchers added innovation in the study to show video animation learning to be more fun, students and ease in understanding material. This study using the experimental methods with the design pre-experimental. After the action in this research, learning outcomes students has increased from pretest to posttest. Based on pretest a raid by researchers, note that the average pretest students only 29,75 or with mastery learning classical 0%, with this 20 students or 100% students have completed. Thus it can be said that the students at the time pretest not maximum. After them doing the pretest, provides treatment students with use the model role playing a video animation as many as 2 meetings. Later in the end of the meeting them doing the posttest and the average value obtaining a 70,8 with mastery learning classical reached 75% or 15 students going and 5 students or 25% students have completed. So it can be said that the results maximum.